A materials perspective on the design of damage-resilient bone implants through additive/advanced manufacturing - Le Ferrand, Hortense (2021)
After more than 5 decades of research, the failure of bone implants is still poorly understood. The aging population makes it increasingly urgent to solve this issue. Among the reasons for failure, catastrophic brittle fracture can be directly related to the implant material and fabrication and deserves more attention. Indeed, clinically available implants do not sufficiently reproduce the hierarchical and heterogeneous microstructural organization of our natural bones, ultimately failing at replicating their mechanical strength and toughness. Nevertheless, recent advances in additive and advanced manufacturing have opened new horizons for the fabrication of biomimetic bone implants, challenging at the same time their characterization, testing, and modeling. This critical review covers selected recent achievements in bone implant research from a materials standpoint and aims at deciphering some of the most urgent issues in this multidisciplinary field.